2005
DOI: 10.1111/j.1439-0523.2005.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AFLP markers linked to one recessive genic male sterility gene in oilseed rape, Brassica napus

Abstract: The commercial utilization of heterosis in seed yield by means of hybrid varieties is of great importance for increasing oilseed rape production in China. This requires a functional system for the production of hybrid seed. The Brassica napus oilseed rape line 9012AB is a recessive epistatic genic male sterility (GMS) two-type line, in which the sterility is controlled by two pairs of recessive duplicate sterile genes (ms1 and ms2) interacting with one pair of a recessive epistatic inhibitor gene (rf). Homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…In turn, these populations can be used as female parents to be pollinated by restorer lines, giving rise to fertile three-way hybrids. This approach for hybrid production greatly overcomes the inevitable restriction of previously reported RGMS lines, such as S45AB and 117AB, in which 50% of the fertile plants would be artificially removed from the female lines before flowering (Chen et al 1998;Ke et al 2005). Thus, the application of 9012AB in hybrid production was widely promoted in China, and a series of commercial cultivars were released .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In turn, these populations can be used as female parents to be pollinated by restorer lines, giving rise to fertile three-way hybrids. This approach for hybrid production greatly overcomes the inevitable restriction of previously reported RGMS lines, such as S45AB and 117AB, in which 50% of the fertile plants would be artificially removed from the female lines before flowering (Chen et al 1998;Ke et al 2005). Thus, the application of 9012AB in hybrid production was widely promoted in China, and a series of commercial cultivars were released .…”
Section: Introductionmentioning
confidence: 94%
“…The RGMS two-type line 9012AB and the temporary maintainer T45 used in our study have been described by Ke et al (2005) and Xie et al (2008), respectively. According to the recently modified hereditary pattern of this RGMS line, the genotypes of 9012A, 9012B and T45 are Bnms3ms3Rf b BnRf b , BnMs3ms3Rf b Rf b and Bnms3ms3Rf c Rf c , respectively (Dong et al 2010).…”
Section: Plant Materials and Recombinant Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these systems, a recessive genic male sterility (RGMS or recessive GMS) line 9012AB (Chen et al 1993) has also been increasingly adopted in China, due to the remarkable advantages including the capability of generating a complete male-sterile population and almost no restriction of restorer (Ke et al 2005;He et al 2008). Initially, the male sterility in 9012AB was regarded to be conditioned by that the interaction of three individual loci (BnMs3, BnMs4 and BnRf) (Chen et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al (2003) identified four sequence-tagged site (STS) markers that are tightly linked to a recessive male-sterile gene in Chinese cabbage; A group of homologs of the male-sterility or fertility gene have been isolated, and the relevant biological functions have been revealed , Cao et al 2006, Jiang and Cao 2007, Tian et al 2009Zhang et al (2008) identified a random amplified polymorphic DNA (RAPD) marker that is tightly linked to a dominant male sterile gene and converted it into a sequence characterized amplified region (SCAR) marker. Wang et al (2000), Ke et al (2005), Yi et al (2006), Hong et al (2006), Lei et al (2007) and Huang et al (2007) identified a set of molecular markers that are linked to the male sterile gene in Brassica napus. Wang et al (2000aWang et al ( , 2000b identified 12 amplified fragment length polymorphism (AFLP) markers, a SCAR marker and an extended random primer amplified region (ERPAR) marker that are closely linked to a dominant male-sterile gene in Brassica oleracea, and mapped the gene to linkage group 09, corresponding to chromosome 3 of B. oleracea.…”
Section: Introductionmentioning
confidence: 99%